Murabaha and its application in Algeria - Guemouh, Mouloud (Journal of Human Sciences, 2022)
Murabaha is one of the most important forms of Islamic finance. In this structure, a financial intermediary buys a good in full ownership, and resells it a little later to a customer who ordered it. This type of contract is not subject to interest, but to a profit margin. Murabaha is divided according to its type into Simple Murabaha and Compound Murabaha or so-called Murabaha for the person ordering the purchase, which is the formula adopted by Islamic banks. Murabaha began in Algeria in the early 1990s, with the entry into activity of the Al Baraka bank in Algeria in 1991, in the absence of a law governing this type of banking activity until the publication of the regulations 20-02 of March 15, 2020 defining banking operations falling under Islamic finance and the conditions for their exercise by banks and financial institutions. This regulation opened the door to this activity for both Islamic and traditional banks, and accordingly we will try in this article to shed light on Murabaha as the most important form of Islamic finance and its application in Algeria.